2015
DOI: 10.1007/s00468-015-1233-0
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove root: adaptations and ecological importance

Abstract: Key message This review gives a comprehensive overview of adaptations of mangrove root system to the adverse environmental conditions and summarizes the ecological importance of mangrove root to the ecosystem. Abstract In plants, the first line of defense against abiotic stress is in their roots. If the soil surrounding the plant root is healthy and biologically diverse, the plant will have a higher chance to survive in stressful conditions. Different plant species have unique adaptations when exposed to a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(103 citation statements)
references
References 124 publications
1
92
1
9
Order By: Relevance
“…The pneumatophores of mangroves of the Arabian Gulf began to branch after an oil spill (Böer 1993), while increased pneumatophore elongation was reported by Saifullah and Elahi (1992) in oil-polluted mangroves of Karachi. These adjustments are likely to maintain oxygen diffusion from aerated root parts to the buried sections and facilitate elimination of by-products of anaerobic respiration which could have been initiated in the buried root section (Srikanth et al 2015).…”
Section: Aerial Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pneumatophores of mangroves of the Arabian Gulf began to branch after an oil spill (Böer 1993), while increased pneumatophore elongation was reported by Saifullah and Elahi (1992) in oil-polluted mangroves of Karachi. These adjustments are likely to maintain oxygen diffusion from aerated root parts to the buried sections and facilitate elimination of by-products of anaerobic respiration which could have been initiated in the buried root section (Srikanth et al 2015).…”
Section: Aerial Rootsmentioning
confidence: 99%
“…The production of numerous feeding roots from new prop roots below the sediment in R. mucronata, buried portions of pneumatophores in A. marina and cable roots in C. tagal have also been observed in flooded trees. According to Srikanth et al (2015), feeding roots, anchor roots, cable roots and pneumatophores (including other types of aerial roots) facilitate gaseous exchange during inundation. Similarly, feeding roots in pneumatophores were observed in mangroves of the Arabian Gulf after the 1991 Gulf war (Böer 1993).…”
Section: Feeding Rootsmentioning
confidence: 99%
“…Since mangrove plants are exposed to adverse conditions such as high salinity, physiological processes of mangrove roots are also an interesting research topic. Srikanth et al (2016), in their review, comprehensively described morphological and physiological characteristics of mangrove roots. As for salt stress tolerance, they discussed recent progresses on molecular mechanisms controlled under salt stress, which could be a key to understand how mangrove plants have adapted to the coastal environments.…”
mentioning
confidence: 99%
“…As for salt stress tolerance, they discussed recent progresses on molecular mechanisms controlled under salt stress, which could be a key to understand how mangrove plants have adapted to the coastal environments. Srikanth et al (2016) also discussed various ecosystem functions of mangrove roots, including flood and sediment control and contribution to biodiversity. Poungparn et al (2016) reported fine root dynamics in secondary mangrove forests in eastern Thailand, which has three vegetation types from river edge to inland (Avicennia, Rhizophora, and Xylocarpus zones).…”
mentioning
confidence: 99%
“…The accessibility to below-ground biomass has limited our knowledge on structural of the anchoring system becomes urgent to better understand and predict their 111 mitigation effect on surges and ecosystem responses to environmental change 112 (Srikanth et al, 2015). As previous studies on terrestrial forests show that the length 113 of lateral roots, and thus the CPRS, increases with tree size (Smith et al, 2014), this 114 study proposes a low-invasive method based on the application of the Doppler effect 115 to detect and measure woody root lengths without digging trenches.…”
Section: Introduction 46 47mentioning
confidence: 99%